Library online cataloging systems (Anmol Pubications, 2001)
Contents of material: 1/ Online catalogues. 2/ Catalogue and the computer. 3/ Information retrieval. 4/ Technical support systems. 5/ The construction and retrieval in online catalogues. 7/ Classification of cataloging.